1968
DOI: 10.1161/01.res.23.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Arrhythmias in the Dog Following Transthoracic Ventricular Defibrillation with Unidirectional Rectangular Stimuli

Abstract: The incidence of the various types of arrhythmia induced by defibrillation in anesthetized dogs that had had continuous ventricular fibrillation for 30 seconds was studied as a function of the current strength and the duration of the unidirectional rectangular pulse used to terminate the fibrillation. Shocks at 10, 20, 40, 80, and 100 amp with durations in the range of 80 fisec through 64 msec were used. At any given energy level the incidence of induced arrhythmias was much larger for the 40-, 80-, and 100-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…16 January, Part I 1993 SGHUDER cess figures substantially independent of animal weight, another 600-episode series [50 A, 4-msec shocks when animals were 100 kg) failed to support our hypothesis that percent success would be independent of body weigbt. Despite an element of ambiguity represented by our experimental results, we continue to believe that the scaling scheme outlined above is informative and probably the best currently availahle.…”
Section: Scalingmentioning
confidence: 61%
See 2 more Smart Citations
“…16 January, Part I 1993 SGHUDER cess figures substantially independent of animal weight, another 600-episode series [50 A, 4-msec shocks when animals were 100 kg) failed to support our hypothesis that percent success would be independent of body weigbt. Despite an element of ambiguity represented by our experimental results, we continue to believe that the scaling scheme outlined above is informative and probably the best currently availahle.…”
Section: Scalingmentioning
confidence: 61%
“…In one sense, it started for us on a sidewalk as I waited for a shuttle bus to return me to my motel or hotel room following an afternoon session of the American Heart Association meeting in Dallas (November [13][14][15][16]1969). As I waited, I reviewed possible projects for future work and among them was the automatic implantable defibrillator!…”
Section: Early Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Studies often cited to support this notion, however, have either failed to provide supporting data (15) or have not controlled peak current independent of energy (16), leaving the two variables confounded and thus preventing separation of cause and effect. One study that carefully controlled energy independent of peak current was reported by Stoeckle et al (17) in 1968. Their data, from experiments with rectangular monophasic defibrillation pulses, indicate that pulses with peak current below a critical level (40 amperes in their canine model) exhibit a rate of post-shock complication (arrhythmia) independent of current but increasing with energy.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 This study was therefore designed to assess the longterm effects of DC shock delivered through an endocardial catheter on regional structure, function, and cardiac rhythm of the canine left ventricle.…”
mentioning
confidence: 99%